An Authoritarian Parenting of Early Childhood in Islamic Perspective: A Case Study in Sleman District, Yogyakarta - Hastuti, Dwi; Siregar, Maragustam; Fatonah, Siti; Miftah, Muhammad (AT-TA'LIM, 2022)
In spite of positive impact in it, authoritarian nursery is essential to be studied because of its negative effect to children This article aims to determine the cause of authoritarian parenting in early childhood in Sleman district. This research was qualitative research with a case study approach. It is a single case study with one research subject. This research is not intended to generalize, but shows the importance of phenomena encountered in other families as well. One case in Sleman district that has implemented authoritarian parenting to her children was showed by tight rules, not involvement of the children to agree with the parents and verbal abuse in harsh words and yelling’s as the punishment. The research result showed that the leading cause of Mrs R committed authoritarian parenting toward her children is caused by several reasons parenting style from the elders who are authoritarian when instilling religious education, the circumstance outside the home that caused parents to be more protective toward their children, the demands of religion-based schools make the parents more rigid to educate their children, and the influence of parents’ diversity background adhered to the particular tenet.